INTERVENSI SOSIAL KOMUNITAS BIRMINGHAM OWNER’S MOTORCYCLE SIANTAR - Ritonga, Fajar Utama; Arifin, Adil; Atika, Tuti (Universitas Medan Area, 2020)
This research purpose to describe the social intervention of the Birmingham Small Arm Owner Motorcycle Siantar (BOM'S) community in fighting for pedicabs with the Birmingham Small Arm (BSA) motorbike brand as a means of transportation for tourists. The research method was carried out with a qualitative approach, the informants in the study were the key informants and 4 main informants. The location of the study was carried out in Pematangsiantar City. The results of this study describe social intervention by the Birmingham Small Arm Owner Motorcycle Siantar (BOM'S) with 4 demands called the